Is there a “victim syndrome” among forced displaced persons in Ukraine? - Timchenko, Olexander; Khrystenko, Vitalii; Lefterov, Vasiliy; Ivanchenko, Andreyanna; Lunov, Vitalii; Pavelkiv, Vitalij (International Journal of Psychosocial Rehabilitation, 2020)
For the first time, a more specific definition is proposed for refugees who are forced to change their place of residence within their own country for reasons beyond their control, due to military conflict or other reasons, namely, “forced displaced persons”. The new definition more fully, correctly and adequately describes the life situation and position of this category of people. This study revealed the negative health effects of forced displaced persons who were resettled to the other region inside Ukraine due to a military conflict in the east of the country. To study both pre-migration traumatic influence and the negative consequences of relocation, three instruments were used: A. Bass and A. Darki technique for diagnosing indicators and forms of aggression, E. Wagner projective hand test and A. M. Etkind’s Relationship Color Test. The results of a sample of Ukrainian forced displaced persons (n=3500) indicate that they have fear, confusion, lack of feeling safety in the near future and dissatisfaction with one of the basic needs – security need. It was established that 7-8% of forced displaced persons have recorded “victim syndrome”, which develops in a situation when a person has lost hope of returning home in the near future and is in a state of constant heightened anxiety. It has been revealed that the “victim syndrome” among forced displaced persons is simultaneously characterized by increased aggressiveness towards others (primarily state structures), as well as the presence of «learned helplessness» and a general negative attitude towards everything that happens in the environment and in life of the refugee. The results of this study will permit to strengthen the potential of the social system in the host community and invest in the planning of health services and the social integration of displaced persons which were resettled not only within the territory of their native country, but also for those who migrated to other national societies.